Activating effect of potassium silicate solution in low portland cement binder. (14th February 2022) - Zhao, Linlin; Ma, Xianwei; Song, Shuaiqi; You, Peibo; Wu, Hairong
Highlights: Potassium silicate solution let low cement binder have high early strength and satisfactory 28-day strength at 10 °C. Revealing the activation mechanism of potassium silicate solution in 70% slag and 30% Portland cement system. Abstract: Sodium silicate solution is usually used as an activating agent of alkali activated material, but easily cause efflorescence and large expansion. Potassium silicate solution (PSS) has not the above problems, but is rarely focused on. The effects of PSS on the strength, shrinkage, and hydration of a low Portland cement binder with 70% slag and 30% Portland cement was studied by XRD, TG, FTIR and 29 Si MAS NMR. It is found that proper amount of PSS can increase the strength and reduce the shrinkage and water absorption of hardened mortar at 10 °C and 95% RH. These effects are ascribed to the contribution of PSS to the transformation of [SiO4 ]n groups in slag.